Teacher Expectations Matter - Papageorge, Nicholas W.; Gershenson, Seth; Kang, Kyung Min (The Review of Economics and Statistics, 2020)
We show that tenth-grade teacher expectations affect students' likelihood of college completion. Our approach leverages a unique feature of a nationally representative dataset: two teachers provided their educational expectations for each student. Identification exploits teacher disagreements about the same student, an idea we formalize using a measurement error model. We estimate an elasticity of college completion with respect to teachers' expectations of 0.12. On average, teachers are overly optimistic, though white teachers are less so with black students. More accurate beliefs are counterproductive if there are returns to optimism or sociodemographic gaps in optimism. We find evidence of both.